The relationship between personality traits and job performance among the staff of University Malaysia Sarawak (UNIMAS) / Farah Afif Muhammad Nureeh - Muhammad Nureeh, Farah Afif (2018)
According to (Rothmann, 2003) job performance is a multi-dimensional construct which indicates how well employees perform their tasks, the initiative they take and the resourcefulness they show in solving problem. The job performance is used as a dependent variable to examine its relationship with the independent variable which is personality traits that consist of agreeableness, conscientiousness and neuroticism towards the staff at University Malaysia Sarawak. The aim of this study is to determine the relationship between personality traits and job performance among the staff at the University Malaysia Sarawak (UNIMAS). This study was accomplished through quantitative method of data collection namely a set of questionnaires. The results of the findings for this study revealed that the personality traits have an effect towards job performance among the staff at University Malaysia Sarawak. The result of the correlation revealed that personality traits have a significant relationship towards job performance. The findings of this study will provide guidelines for the management on how to increase the employee’s job performance in the organization. It is recommended for future researchers that an alternative method of data collection to be employed to obtain in-depth information on how personality trait can effect an employee job performance.